2003
DOI: 10.1093/deafed/8.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Residential and Day Schools for Deaf Students in the United States That Identify Themselves as Bilingual-Bicultural Programs

Abstract: The purpose of this survey was to determine how many residential and day schools for deaf and hard-of-hearing students in the United States described themselves as bilingual-bicultural (BiBi) programs and to describe characteristics of those programs related to initial implementation, whether a single language (e.g., English or ASL) is promoted as the first language (L1) and the language of instruction for all deaf students, how English is conveyed conversationally to deaf students, the quality of ASL abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In her educational placement, she was provided with a deaf teacher of the deaf who used a manual Pidgin-English-ASL approach to instruction. (Lack of consistent use of ASL is not uncommon among teachers of the deaf [LaSasso & Lollis, 2003].) The participant passed a vision screening within 1 year before beginning research.…”
Section: Participantsmentioning
confidence: 99%
“…In her educational placement, she was provided with a deaf teacher of the deaf who used a manual Pidgin-English-ASL approach to instruction. (Lack of consistent use of ASL is not uncommon among teachers of the deaf [LaSasso & Lollis, 2003].) The participant passed a vision screening within 1 year before beginning research.…”
Section: Participantsmentioning
confidence: 99%
“…The ASL-signing deaf child can then be considered a member of a bilingual minority learning to read and write in English (Charrow & Wilbur, 1975/1989), a viewpoint reflected in the bilingual-bicultural (Bi-Bi) educational philosophy. Bilingual bimodal educational approaches, envisaged to support academic success of DHH children (LaSasso & Lollis, 2003;Strong, 1995), were first introduced in the late 1980s in the United States and in other counties such as Sweden (Svartholm, 2010), Denmark (Hansen, 1994), and United Kingdom (Swanwick & Gregory, 2007). The ASL/ English bilingual programs aim to provide education to deaf and hearing students that emphasizes language abilities across three domains-signacy, literacy, and oracy.…”
mentioning
confidence: 99%
“…These future teachers entered the workforce with limited opportunities for understanding and interacting with the Deaf community and without the necessary tool kit to help deaf students develop into creative, highly educated, socially mature bilingual adults. These studies showed a clear mismatch between programs that prepared future teachers of deaf children and the growing focus of bilingual deaf education programs in K-12 environments (LaSasso & Lollis, 2003;Strong, 1995). Even our own graduates have provided feedback about their need for additional training in ASL/English bilingual teaching methods, demonstrating the link between what is happening in the schools and what we as faculty in deaf education teacher training programs need to do.…”
Section: Transformation Neededmentioning
confidence: 98%